Potential of mesenchymal stem cells alone, or in combination, to treat traumatic brain injury. (10th March 2020) - Willing, Alison E.; Das, Mahasweta; Howell, Mark; Mohapatra, Shyam S.; Mohapatra, Subhra
Abstract: Traumatic brain injury (TBI) causes death and disability in the United States and around the world. The traumatic insult causes the mechanical injury of the brain and primary cellular death. While a comprehensive pathological mechanism of TBI is still lacking, the focus of the TBI research is concentrated on understanding the pathophysiology and developing suitable therapeutic approaches. Given the complexities in pathophysiology involving interconnected immunologic, inflammatory, and neurological cascades occurring after TBI, the therapies directed to a single mechanism fail in the clinical trials. This has led to the development of the paradigm of a combination therapeutic approach against TBI. While there are no drugs available for the treatment of TBI, stem cell therapy has shown promising results in preclinical studies. But, the success of the therapy depends on the survival of the stem cells, which are limited by several factors including route of administration, health of the administered cells, and inflammatory microenvironment of the injured brain. Reducing the inflammation prior to cell administration may provide a better outcome of cell therapy following TBI. This review is focused on different therapeutic approaches of TBI and the present status of the clinical trials.